2017
DOI: 10.1111/cas.13244
|View full text |Cite
|
Sign up to set email alerts
|

M2‐like macrophage polarization in high lactic acid‐producing head and neck cancer

Abstract: Reprogramming of glucose metabolism in tumor cells is referred to as the Warburg effect and results in increased lactic acid secretion into the tumor microenvironment. We have previously shown that lactic acid has important roles as a pro‐inflammatory and immunosuppressive mediator and promotes tumor progression. In this study, we examined the relationship between the lactic acid concentration and expression of LDHA and GLUT1, which are related to the Warburg effect, in human head and neck squamous cell carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 40 publications
5
80
0
Order By: Relevance
“…Lactate prevents cytokine release and monocyte migration, while promotes the formation of tumor-associated macrophage 2 (TAM2) phenotype. It leads to upregulate the expression of arginase 1, promote immune escape and tumor progression (25,(76)(77)(78). Lactate reduces the production of IFN-γ from T cells and NK cells, and decreases the level of nuclear factor of activated T cells (NFAT), which also contributes to immune escape and tumor progression (79,80).…”
Section: Glucose Metabolism and Tumor Microenvironment (Tme)mentioning
confidence: 99%
“…Lactate prevents cytokine release and monocyte migration, while promotes the formation of tumor-associated macrophage 2 (TAM2) phenotype. It leads to upregulate the expression of arginase 1, promote immune escape and tumor progression (25,(76)(77)(78). Lactate reduces the production of IFN-γ from T cells and NK cells, and decreases the level of nuclear factor of activated T cells (NFAT), which also contributes to immune escape and tumor progression (79,80).…”
Section: Glucose Metabolism and Tumor Microenvironment (Tme)mentioning
confidence: 99%
“…To further validate, we tested the ability of CHI3L1 to promote M2 differentiation in vitro. As Arg-1 and Ym-1 are consistently expressed by M2 macrophage, 30,31 we stimulated macrophage with recombinant CHI3L1 and M2 markers (Ym-1 and Arg-1) were subsequently identified by immune staining and Western blot (Figs. 3B-D).…”
Section: Chi3l1 Promotes Neovascularization By Inducing Macrophage M2mentioning
confidence: 99%
“…Moreover, studies show the correlation between the density of CAFs and TAMs with poor outcome in HNSCC (59,60). Furthermore, one study reported that protumorigenic macrophage polarization is promoted in HNSCC tumors with high lactic acid concentrations (61). Interestingly, CS fibroblasts in our model secrete much higher lactate than CTRL fibroblasts.…”
Section: Discussionmentioning
confidence: 58%